Serum proteins and leucocytes differential count in the common carp (Cyprinus carpio L.) infested with ectoparasites - Ahmed , S.M.; Ali, A.H. (Mesopotamian Journal of Marine Sciences, 2022)
A total of 48 Pond reared common carp C. carpio ranged between 2.5-11.8 cm in total length were obtained from University of Basrah's fish farm during May-June 2011. It was investigated for parasites, and it was infested with four different groups of ectoparasites, including Ciliophora (Ichthyophthirius multifiliis and Trichodina sp.), Monogenoidea (Dactylogyrus spp. and Gyrodactylus sp.), Trematoda (Ascocotyle coleostoma metacercariae) and Crustacea (Dermoergasilus sp. and Lernaea sp. copepodid larval stage). Differential count of leucocytes, total protein level, albumin and globulin in blood serum were determined in healthy (non-infested) and infested fish. No significant differences (p>0.05) have been reported between infested and non-infested fish in all blood parameters except in monocyte counts of the third group (infested with two species of Ciliophora) and sixth group (double infestation between A. coleostoma and Dermoergasilus sp.). This study showed that common carp can withstand different light and mild infestation of ectoparasites. We can considered common carp among a fish category having very good resistibility towards ectoparasites.